Public perceptions of the Perth Drug Court as a mechanism for dealing with drug related crime - Jordan, Dominic (2015)
In the last two decades, drug courts have been introduced throughout Australia, to address the issue of drug related crime. Drug courts aim to reduce criminal recidivism by placing drug dependent offenders into intensive supervision and treatment programs. Research has revealed that drug courts, including the Perth Drug Court, can reduce criminal recidivism in offenders for whom drug use is a dynamic risk factor for their criminal behaviour. Currently however, little is known about the public’s knowledge and perceptions of drug courts. The aim of the current study was to determine the perceptions of a sample of the Western Australian public, in relation to the Perth Drug Court as a way of dealing with drug related crime. The current study was exploratory and qualitative, and involved an inductive thematic analysis of secondary data collected as part of an undergraduate research unit at Edith Cowan University. A semi-structured interview approach was applied to explore participants’ (n= 33) perceptions about drug use, crime and the Perth Drug Court in-depth. During the interview participants were provided with some brief, contextual information regarding the Perth Drug Court, in order to place their perceptions in a more accurate context. The findings revealed that members of the public have punitive attitudes towards drug dependent offenders and lack knowledge about alternative justice strategies such as the Perth Drug Court. However, despite this, many participants felt that the Perth Drug Court would be effective in reducing drug related criminal recidivism, thus showing some support for the concept. The findings of the current study provide an understanding of how a sample of the Western Australian public view the Perth Drug Court, which can inform further research regarding public perceptions of drug courts, and other alternative justice strategies